Biotechnological tools boost the functional diversity of DNA-based data storage systems - Xiaoyuan Xu; Wen Wang; Zhi Ping (Computational and Structural Biotechnology Journal)
DNA-based data storage has emerged as a groundbreaking solution to the growing demand for efficient, high-density, and long-term data storage. It is attracting many researchers’ attention, who are implementing functions such as random access, searching, and data operations apart from the existing capabilities, including reading and writing. We summarize the recent progress of how biotechnological tools, based on sequence specificity, encapsulation, and high-dimensional structures of DNA molecules, facilitate the implementation of various functions. The limitations of using biochemical reactions that hinder the development of more precise and efficient information storage systems are also discussed. Future advancements in molecular biology and nanotechnology are expected to improve the architecture, scalability, and efficiency of DNA storage, positioning it as a sustainable and dynamic alternative to conventional data storage systems.